Inclusion of patient-centered, non-microbiological endpoints and biomarkers in tuberculosis drug trials - DiNardo, Andrew R.; Sabiiti, Wilbert; Gillespie, Stephen H.; Georghiou, Sophia B.; Heinrich, Norbert; Hittel, Norbert; Taghlabi, Sami; Carrero Longlax, Danna; Kohli, Mikashmi; Panzner, Ursula; Musia, Collins; Lange, Christoph; et al. (Frontiers in Antibiotics, 2025)
Tuberculosis drug trials are primarily designed to identify antibiotic regimens with the strongest potency to kill Mycobacterium tuberculosis. However, microbiologic cure is not synonymous with improved health and recovery. Beyond antimicrobial efficacy, parameters such as morbidity and mortality related to lung function, cardiovascular health, and cancer should be prioritized. This narrative review emphasizes the critical need to emphasize clinical outcomes as much, if not more, than microbiological endpoints. We examine the underlying pathophysiological mechanisms and determinants of non-microbiological outcomes in tuberculosis, providing a synthesis of current knowledge. While there is growing evidence for some biomarkers to risk stratify TB patients for risk of all-cause mortality, relapse, or lung damage, no evidence was found on TB-associated cancer or cardiovascular disease. In addition to monitoring microbiologic outcomes, clinical trials and treatment cohorts need to capture patient-centered health dimensions more broadly. Finally, we highlight key research gaps and opportunities to evaluate non-microbiological biomarkers, aiming to improve patient monitoring and enable stratified approaches to tuberculosis management.